Hector Vigliecca and social housing proposals: building urban landscape - Machado, Andréia; Gonsales, Celia (National Journal of City Management, 2022)
This article analysis the construction of urban landscape through housing, more specifically, social housing in the work of architect Hector Vigliecca, and aims to analyze the architect’s social housing projects, seeking to understand the design strategies used to establish a very consistent relationship between architecture and the city, that is, the strategies used to “build the city”.